Adjuvants are Key Factors for the Development of Future Vaccines: Lessons from the Finlay Adjuvant Platform - Pérez, Oliver; Romeu, Belkis; Cabrera, Osmir; Gonzalez, Elizabeth; Batista-Duharte, Alexander; Labrada, Alexis; Pérez, Rocmira; Reyes, Laura; Ramírez, Wendy; Sifontes, Sergio; Fernández, Nelson; Lastre, Miriam (Frontiers in Immunology, 2013)
The development of effective vaccines against neglected diseases, especially those associated with poverty and social deprivation, is urgently needed. Modern vaccine technologies and a better understanding of the immune response have provided scientists with the tools for rational and safer design of subunit vaccines. Often, however, subunit vaccines do not elicit strong immune responses, highlighting the need to incorporate better adjuvants; this step therefore becomes a key factor for vaccine development. In this review we outline some key features of modern vaccinology that are linked with the development of better adjuvants. In line with the increased desire to obtain novel adjuvants for future vaccines, the Finlay Adjuvant Platform offers a novel approach for the development of new and effective adjuvants. The Finlay Adjuvants (AFs), AFPL (proteoliposome) and AFCo (cochleate), were initially designed for parenteral and mucosal applications, and constitute potent adjuvants for the induction of Th1 responses against several antigens. This review summarizes the status of the Finlay technology in producing promising adjuvants for unsolved-vaccine diseases including mucosal approaches and therapeutic vaccines. Ideas related to adjuvant classification, adjuvant selection, and their possible influence on innate recognition via multiple toll-like receptors are also discussed.